Diseño y construcción de una batería de bombeo en el laboratorio de procesos unitarios de la FIQ-UNAP - Mendoza Vergara, Gustavo Leonardo (2024)
Series and parallel pump configurations are used in pumping systems to improve efficiency and performance. In a series configuration, multiple pumps are placed in line, so that the output flow of one pump is directed to the input of the next pump. This increases the total pressure generated by the pumps, which is useful in applications where greater thrust is required. On the other hand, in a parallel configuration, multiple pumps are connected so that their output flows combine in a common pipe. This increases the total flow capacity of the system, which is beneficial in situations where large volumes of liquid need to be moved. The general objective of this study was to design, build, and put into operation a battery of pumps with series and parallel arrangements in the Chemical Engineering Faculty of the UNAP, in order to perform graphical and analytical determinations of flow rates and pressures. The quantitative research was experimental in nature, and 8 tests were conducted on the pump battery with series and parallel arrangements. It was determined that the pumping battery has a high percentage of error in the parallel arrangement configuration when comparing the theoretical total dynamic head to the experimental dynamic head. This is due to the presence of more accessories and length in that arrangement, causing greater energy loss. On the other hand, there is a lower percentage of error in the series arrangement configuration when comparing the theoretical total dynamic head to the experimental dynamic head. This is attributed to the fewer accessories and less length in that arrangement, resulting in less energy loss.